Physical-aware pattern selection for stuck-at faults (2017)
The stuck-at faults are basic faults that fail the chips. Various defects in the circuit can develop into stuck-at faults. To detect more defects caused by stuck-at faults, some of the fault sites may need to be detected multiple times. Thus, the existing pattern generation techniques provide N-detect ATPG, where each fault site would not be removed from the fault list before it is detected for N times. The "N" value is determined empirically by the criticality of the application. The N-detect test has been shown to have a higher quality of detecting defects. However, the traditional N-detect test does not necessarily exploit the localized characteristics of defects. In addition, it may result in a large number of patterns. In this paper, we present a test pattern selection procedure to optimize the N-detect pattern generation by differentiating the fault sites according to the physical details and generate patterns that have comparable defect detection quality with N-detect pattern generation. © 2017 IEEE.